Nanometer ZSM-5 molecular sieve and preparation method and application thereof
Through a simplified preparation method, nano ZSM-5 molecular sieve was successfully prepared using materials such as silicone sources and silica particles, which solved the problems of high production costs, serious environmental pollution and difficult recycling in the existing technology, and achieved efficient and environmentally friendly nano molecular sieve preparation and catalytic activity improvement.
Patent Information
- Application Number
- CN202311394933.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-10-25
- Publication Date
- 2025-04-25
AI Technical Summary
In the prior art, when preparing nano ZSM-5 molecular sieve, molecular sieve growth regulators and organic template agents are used, resulting in high production costs, serious environmental pollution, and difficult to recover nanomolecular sieves.
Through a simple preparation method, the seed mother liquor is formed by mixing silicone sources, ethanol and water, and then compounded with silica particles and aluminum sources, and undergo multiple crystallization reactions to form a nano ZSM-5 molecular sieve. This method simplifies the process without the need for a large number of template agents and growth regulators.
The efficient preparation of nano ZSM-5 molecular sieve is achieved, which reduces production costs, simplifies the process flow, and improves catalytic activity by introducing mesoporous structures. The surface of nano ZSM-5 molecular sieve is highly hydrophobic and easy to filtration and recycling.
Smart Images

Figure CN119873855A_ABST
Abstract
Description
Technical Field
[0001] The present disclosure relates to molecular sieve synthesis technology, and in particular, to a nano ZSM-5 molecular sieve and a preparation method and application thereof. Background Art
[0002] In order to alleviate the mass transfer limitations of traditional microporous molecular sieves, a large number of studies have been devoted to the preparation of nanomolecular sieves with smaller particle sizes.
[0003] A commonly used method for preparing small-grain molecular sieves is to use a molecular sieve growth modifier (ZGM). A molecular sieve growth modifier refers to a small molecule or polymer substance that can regulate the anisotropic growth rate of a crystal by physically adsorbing on a specific crystal plane. Its typical feature is that the interaction between the modifier and the crystal plane is a selective adsorption to a specific crystal plane based on molecular recognition. Common ZGMs include metals, metal oxides, and polymers. For example, Rimer et al. used electrically neutral modifiers PEIM, CTAB, 1,6-hexanediol, etc. to successfully prepare small-grain molecular sieves less than 300nm (J.Am.Chem.Soc.2015,137,40,13007–13017). However, the molecular sieve product obtained by the above method involves the use of a molecular sieve growth modifier and an organic template. The use of an external molecular sieve growth modifier and a large amount of organic template greatly increases the production cost, and will increase the release of VOCs during the product post-processing roasting process, causing environmental problems.
[0004] When the molecular sieve grain size is too small (less than 400nm), due to the accumulation of molecular sieve grains and the capillary action of the water liquid surface, the pore size does not match the water molecule size, and then the water molecules condense between the molecular sieves to cause blockage, making it difficult for the molecular sieve to be collected by filtering methods. This problem will significantly increase the production cost and limit the production and application of small-grain molecular sieves. A large number of studies are devoted to maintaining the performance of nano molecular sieves, making the molecular sieve product easier to recover. For example, Yu Han et al. used triblock copolymer F127 to assemble 100nm nano molecular sieves into micron-sized aggregates during the synthesis process (Chem. Mater., 2009, 21, 2344); Tang Yi et al. used urea-formaldehyde polymer polymerization to induce the assembly of nano molecular sieves to form microspheres (Chem. Mater. 2006, 18, 1861-1866). CN102872909A reports the use of mesoporous particles with positive charges on the surface to bond molecular sieve nanoparticles with negative charges on the surface, and the nano molecular sieve aggregates are obtained by combining the electrostatic action between the molecular sieve nanoparticles and the mesoporous particles. The above technologies all obtain nano-molecular sieve aggregates to facilitate molecular sieve filtration and recovery, and the molecular sieve molding process uses organic matter to assemble the synthesized molecular sieves, which requires post-processing to remove the organic materials. The method is relatively cumbersome, the raw material cost is high, and the post-processing step has high energy consumption. Summary of the invention
[0005] The purpose of the present disclosure is to provide a nano ZSM-5 molecular sieve and a preparation method and application thereof. The method makes the surface of the nano ZSM-5 molecular sieve product more hydrophobic and can be easily filtered and recovered without forming aggregates. At the same time, the preparation method is simple and the process is simple, and no multi-step synthesis is required, which greatly saves production costs.
[0006] In order to achieve the above object, the present disclosure provides a method for preparing a nano ZSM-5 molecular sieve in a first aspect, the method comprising the following steps:
[0007] (1) mixing an organosilicon source, ethanol and water for a first mixing, and then adding a template for a second mixing to obtain a seed crystal mother solution; subjecting the seed crystal mother solution to a first crystallization reaction, and separating seed crystals from the obtained material;
[0008] (2) performing a third mixing of the seed crystals, silica particles and water to obtain a mixed solution, filtering the mixed solution, and drying and performing a first calcination treatment on the filtered solid to obtain seed crystal silica composite particles;
[0009] (3) mixing an aluminum source, an alkali source and water for a fourth mixing, and then adding the seed silicon dioxide composite particles for a fifth mixing to obtain a crystallization precursor solution;
[0010] (4) subjecting the crystallization precursor solution to a second crystallization reaction and a third crystallization reaction in sequence, wherein the temperature of the second crystallization reaction is higher than the temperature of the third crystallization reaction by more than 30° C.;
[0011] In step (2), the average particle size of the silica particles is less than 100 μm, and the mesoporous specific surface area of the silica particles is 80 to 200 m 2 / g; the weight ratio of the silicon dioxide particles to the seed crystals is 5-30:1.
[0012] Optionally, in step (1), the first mixing conditions include: stirring at a temperature of 20-35° C. for 0.5-2 h; the second mixing conditions include: stirring at a temperature of 50-80° C. for 4-8 h;
[0013] In step (1), SiO 2 The molar ratio of the organosilicon source, the ethanol, the template and the water is 1:(3.2-4.8):(0.16-0.24):(48-72);
[0014] The conditions of the first crystallization reaction include: the first crystallization is dynamic crystallization or static crystallization, the temperature is 110-130° C., and the time is 16-72 hours;
[0015] The organic silicon source is orthosilicate, and the orthosilicate is selected from one or more of tetraethyl orthosilicate and methyl orthosilicate;
[0016] The template agent is a quaternary ammonium compound, and the quaternary ammonium compound is selected from one or more of tetrapropylammonium hydroxide, tetraethylammonium hydroxide and tetramethylammonium hydroxide.
[0017] Optionally, in step (2), the weight ratio of the silicon dioxide particles to the seed crystals is 15-25:1; the mesoporous specific surface area of the silicon dioxide particles is 90-180 m 2 / g;
[0018] The third mixing conditions include: temperature of 20-35°C and time of 0.5-2h;
[0019] The conditions of the first calcination treatment include: a calcination temperature of 500 to 800° C. and a calcination time of 4 to 8 hours.
[0020] Optionally, in step (3), the fourth mixing conditions include: stirring at a temperature of 20-35°C for 0.5-2h; the fifth mixing conditions include: stirring at a temperature of 50-80°C for 2-4h.
[0021] Optionally, in step (3), the aluminum source is an aluminum-containing compound selected from one or more of sodium aluminate, aluminum chloride, aluminum sulfate, aluminum isopropoxide and aluminum nitrate; and the alkali source is selected from one or more of sodium hydroxide and potassium hydroxide.
[0022] Optionally, in step (3), SiO 2 The seed silica composite particles are calculated as Al 2 O 3 The aluminum source is calculated as Na 2 The molar ratio of the alkali source to the water is 1:(0.012-0.018):(0.12-0.18):(25-37.5).
[0023] Optionally, in step (4), the conditions of the second crystallization reaction include: temperature of 190-220°C, time of 0.5-3h, and the second crystallization reaction is dynamic crystallization; the conditions of the third crystallization reaction include: temperature of 150-180°C, time of 6-15h, and the third crystallization reaction is dynamic crystallization; the temperature of the second crystallization reaction is 30-50°C higher than the temperature of the third crystallization reaction.
[0024] Optionally, the method further comprises: filtering, washing, drying and performing a second calcination treatment on the product obtained in step (4) in sequence; the conditions of the second calcination treatment include: a temperature of 500-600° C. and a time of 4-8 hours.
[0025] The second aspect of the present disclosure provides a nano ZSM-5 molecular sieve prepared by the method described in the first aspect of the present disclosure.
[0026] The third aspect of the present disclosure provides a nano ZSM-5 molecular sieve, which is formed into particles, and a single particle is in the shape of a hexagonal prism, the side length of the hexagonal cross-section is 150 to 200 nm, and the height of the hexagonal prism is 125 to 150 nm; the average particle size of the nano ZSM-5 molecular sieve is 100-500 nm.
[0027] Optionally, the mass fraction of the nano ZSM-5 molecular sieve is 60-95% based on crystallinity; the micropore volume of the nano ZSM-5 molecular sieve is 0.07-0.15 cm 3 / g, and the mesopore volume is 0.06-0.12cm 3 / g.
[0028] The fourth aspect of the present disclosure provides the use of the nano ZSM-5 molecular sieve described in the second aspect of the present disclosure or the third aspect of the present disclosure in a catalytic cracking reaction.
[0029] Through the above technical scheme, the method disclosed in the present invention obtains seed silicon dioxide composite particles by compounding seed crystals and silicon dioxide particles, and adjusts the synthesis conditions to obtain nano molecular sieve grains. The synthesis method disclosed in the present invention is simple and the process is simple, and there is no need for multi-step synthesis, which greatly saves production costs. The active component dispersion of the nano ZSM-5 molecular sieve disclosed in the present invention is high. On the basis of maintaining the microporous structure of the nano molecular sieve, strengthening mass transfer and diffusion, and improving the wear resistance of the molecular sieve, intercrystalline stacking mesopores are introduced, which further reduces the diffusion limitation and improves the catalytic activity of the molecular sieve material. The nano ZSM-5 molecular sieve obtained by the method disclosed in the present invention does not need to be formed into molecular sieve aggregates, and the surface of the product has a certain concentration of silanol groups to make it more hydrophobic, more conducive to water penetration and easy to filter.
[0030] Other features and advantages of the present disclosure will be described in detail in the following detailed description. BRIEF DESCRIPTION OF THE DRAWINGS
[0031] The accompanying drawings are used to provide a further understanding of the present disclosure and constitute a part of the specification. Together with the following specific embodiments, they are used to explain the present disclosure but do not constitute a limitation of the present disclosure. In the accompanying drawings:
[0032] Figure 1 This is the XRD diagram of the product obtained in Example 1 of the present disclosure.
[0033] Figure 2 This is a scanning electron microscope image of the product obtained in Example 1 of the present disclosure.
[0034] Figure 3 This is the isothermal adsorption curve of the product obtained in Example 1 of the present disclosure.
[0035] Figure 4 This is a scanning electron microscope image of the product obtained in Comparative Example 1 of the present disclosure.
[0036] Figure 5 This is a scanning electron microscope image of the product obtained in Comparative Example 2 of the present disclosure.
[0037] Figure 6 This is a scanning electron microscope image of the product obtained in Comparative Example 3 of the present disclosure. DETAILED DESCRIPTION
[0038] The specific implementation of the present disclosure is described in detail below in conjunction with the accompanying drawings. It should be understood that the specific implementation described herein is only used to illustrate and explain the present disclosure, and is not used to limit the present disclosure.
[0039] The first aspect of the present disclosure provides a method for preparing a nano ZSM-5 molecular sieve, the method comprising the following steps:
[0040] (1) mixing an organosilicon source, ethanol and water for a first mixing, and then adding a template for a second mixing to obtain a seed crystal mother solution; subjecting the seed crystal mother solution to a first crystallization reaction, and separating seed crystals from the obtained material;
[0041] (2) performing a third mixing of the seed crystals, silica particles and water to obtain a mixed solution, filtering the mixed solution, and drying and performing a first calcination treatment on the filtered solid to obtain seed crystal silica composite particles;
[0042] (3) mixing an aluminum source, an alkali source and water for a fourth mixing, and then adding the seed silicon dioxide composite particles for a fifth mixing to obtain a crystallization precursor solution;
[0043] (4) subjecting the crystallization precursor solution to a second crystallization reaction and a third crystallization reaction in sequence, wherein the temperature of the second crystallization reaction is higher than the temperature of the third crystallization reaction by more than 30° C.;
[0044] In step (2), the average particle size of the silica particles is less than 100 μm, and the mesoporous specific surface area of the silica particles is 80 to 200 m 2 / g; the weight ratio of the silicon dioxide particles to the seed crystals is 5-30:1.
[0045] The present invention adopts solid-phase silicon source to in-situ synthesize nano ZSM-5, and introduces intercrystalline stacked mesopores on the basis of maintaining the microporous structure of nano molecular sieve, strengthening mass transfer diffusion, and improving the wear resistance of molecular sieve. At the same time, due to the interaction between the repulsive force between the hydrophobic groups of the template agent and the Coulomb force on the surface of a single nano-grain, the formation of intercrystalline stacked mesopores is further promoted, the diffusion limitation is further reduced, and the catalytic activity of the molecular sieve material is improved.
[0046] The nano ZSM-5 molecular sieve obtained by the present disclosure has high conversion activity in macromolecular cracking reaction, has high macromolecular catalytic cracking activity and high deep cracking product yield. The nano ZSM-5 molecular sieve disclosed by the present disclosure has a certain content of silanol groups on the surface to make it more hydrophobic, and product separation can be achieved by simple filtration. In addition, the present invention uses a seed crystal method to avoid the large-scale use of templates, further reduce production costs, and contribute to industrial promotion and application.
[0047] According to one embodiment of the present disclosure, in step (1), the first mixing conditions include: stirring at a temperature of 20-35°C for 0.5-2h; the second mixing conditions include: stirring at a temperature of 50-80°C, preferably 60-70°C, for 4-8h, preferably 5-7h; in step (1), SiO 2The molar ratio of the organosilicon source, the ethanol, the template and the water is 1: (3.2-4.8): (0.16-0.24): (48-72), preferably 1: (3.5-4.5): (0.17-0.23): (52-68); the conditions of the first crystallization reaction include: the first crystallization is dynamic crystallization or static crystallization, the temperature is 110-130°C, preferably 115-125°C, and the time is 16-72h, preferably 24-60h; the organosilicon source is orthosilicate, and the orthosilicate is selected from one or more of tetraethyl orthosilicate and methyl orthosilicate; the template is a quaternary ammonium compound, and the quaternary ammonium compound is selected from one or more of tetrapropylammonium hydroxide, tetraethylammonium hydroxide and tetramethylammonium hydroxide. The above-mentioned implementation method is conducive to obtaining a nano ZSM-5 molecular sieve with high crystallinity and large micropore volume, which has higher macromolecular catalytic cracking activity and higher product yield when used for catalytic cracking.
[0048] According to one embodiment of the present disclosure, in step (2), the weight ratio of the silicon dioxide particles to the seed crystals is 15-25:1; the silicon dioxide particles are preferably SiO 2 Silica microspheres with a weight content of more than 95%; the mesoporous specific surface area of the silica particles is 90 to 180 m 2 / g; the third mixing conditions include: temperature of 20-35°C, time of 0.5-2h; the first calcination conditions include: calcination temperature of 500-800°C, preferably 550-750°C, calcination time of 4-8h, preferably 5-7h. The above implementation is conducive to obtaining a nano ZSM-5 molecular sieve with high crystallinity and large micropore volume, which has higher macromolecular catalytic cracking activity and higher product yield when used for catalytic cracking.
[0049] According to one embodiment of the present disclosure, the average particle size of the silicon dioxide particles can be greater than 100 μm, and the ground silicon dioxide particles are obtained by fully grinding the silicon dioxide particles, so that the particle size of the ground silicon dioxide particles is less than 100 μm, preferably 5-100 μm, and more preferably 5-95 μm. In one embodiment, the grinding is completed by a ball mill, for example, a planetary ball mill is used, the ball milling time is 1 to 5 hours, and the rotation speed is 100 to 500 rpm. Planetary ball mills are well known to those skilled in the art, such as the JC-QM series vertical planetary ball mill of Juchuang Environmental Protection.
[0050] According to an embodiment of the present disclosure, in step (3), the fourth mixing conditions include: under stirring, the temperature is 20-35°C, and the time is 0.5-2h; the fifth mixing conditions include: under stirring, the temperature is 50-80°C, preferably 60-70°C, and the time is 2-4h, preferably 2.5-3.5h. The above embodiment is conducive to obtaining a nano ZSM-5 molecular sieve with high crystallinity and large micropore volume, which has higher macromolecular catalytic cracking activity and higher product yield when used for catalytic cracking.
[0051] According to one embodiment of the present disclosure, in step (3), the aluminum source is an aluminum-containing compound selected from one or more of sodium aluminate, aluminum chloride, aluminum sulfate, aluminum isopropoxide and aluminum nitrate; and the alkali source is selected from one or more of sodium hydroxide and potassium hydroxide.
[0052] According to one embodiment of the present disclosure, in step (3), SiO 2 The seed silica composite particles are calculated as Al 2 O 3 The aluminum source is calculated as Na 2 The molar ratio of the alkali source to the water is 1: (0.012-0.018): (0.12-0.18): (25-37.5), preferably 1: (0.013-0.017): (0.12-0.18): (27.5-35). The above embodiment is conducive to obtaining a nano ZSM-5 molecular sieve with high crystallinity and large micropore volume, which has higher macromolecular catalytic cracking activity and higher product yield when used for catalytic cracking.
[0053] According to one embodiment of the present disclosure, the pH value of the crystallization precursor solution is 10-12.
[0054] According to an embodiment of the present disclosure, in step (4), the conditions of the second crystallization reaction include: a temperature of 190-220°C, preferably 200-210°C, a time of 0.5-3h, preferably 1-2.5h, and the second crystallization reaction is dynamic crystallization; the conditions of the third crystallization reaction include: a temperature of 150-180°C, preferably 155-170°C, a time of 6-15h, preferably 7-14h, and the third crystallization reaction is dynamic crystallization; the temperature of the second crystallization reaction is 30-50°C higher than the temperature of the third crystallization reaction. The above embodiment is conducive to obtaining a nano ZSM-5 molecular sieve with high crystallinity and large micropore volume, which has higher macromolecular catalytic cracking activity and higher product yield when used for catalytic cracking.
[0055] According to one embodiment of the present disclosure, the method further comprises: filtering, washing, drying and performing a second calcination treatment on the product obtained in step (4) in sequence; the conditions of the second calcination treatment comprise: a temperature of 500-600°C, preferably 520-580°C, and a time of 4-8h, preferably 5-7h.
[0056] The second aspect of the present disclosure provides a nano ZSM-5 molecular sieve prepared by the method described in the first aspect of the present disclosure.
[0057] The third aspect of the present disclosure provides a nano ZSM-5 molecular sieve, which is formed into particles, and a single particle is in the shape of a hexagonal prism, the side length of the hexagonal cross-section is 150 to 200 nm, and the height of the hexagonal prism is 125 to 150 nm; the average particle size of the nano ZSM-5 molecular sieve is 100-500 nm.
[0058] According to one embodiment of the present disclosure, the mass fraction of the nano ZSM-5 molecular sieve is 60-95% based on crystallinity; the micropore volume of the nano ZSM-5 molecular sieve is 0.07-0.15 cm 3 / g, and the mesopore volume is 0.06-0.12cm 3 / g.
[0059] The fourth aspect of the present disclosure provides the use of the nano ZSM-5 molecular sieve described in the second aspect of the present disclosure or the third aspect of the present disclosure in a catalytic cracking reaction.
[0060] The present invention is further illustrated by the following examples, but the present invention is not limited thereto.
[0061] The tetraethyl orthosilicate (TEOS) used in the present disclosure was purchased from Inotech, product number A69114; the tetrapropylammonium hydroxide (TPAOH) used was purchased from Inotech, product number A64568. Unless otherwise specified, the other reagents were commercially available.
[0062] In the embodiments and comparative examples, the average particle size of the nano ZSM-5 molecular sieve is obtained by randomly measuring the sizes of 20 ZSM-5 molecular sieves in an electron microscope (Hitachi scanning electron microscope, S-4800) image using Nano Measurer software. In the measurement process, the size of a ZSM-5 molecular sieve is the straight-line distance obtained by connecting the two farthest endpoints on the particle in the electron microscope image.
[0063] The average particle size of the nano ZSM-5 molecular sieve and the average particle size of the silica particles are equivalent volume diameters obtained by laser particle size method, and the testing instrument is Malvern Mastersizer 3000.
[0064] The relative crystallinity refers to the ASTM D3906-03 standard, and the ratio of the characteristic peak area of the crystallized product XRD spectrum at 2θ angle between 22.5-25.0° to the characteristic peak area of the standard molecular sieve is defined as the relative crystallinity. The test instrument is a D5005 X-ray diffractometer from Siemens, Germany. The test conditions are Cu target, Kα radiation, solid detector, tube voltage 40kV, tube current 40mA, step scan, step width 0.02°, prefabrication time 2s, and 2θ scanning range 5°~70°.
[0065] The pore size distribution is measured by low-temperature nitrogen adsorption capacity method, and the testing instrument is ASAP2400 static nitrogen adsorption instrument of Micromeritics Company; the testing conditions are that the sample is vacuum degassed at 1.33Pa and 300°C for 4h, and then contacted with liquid nitrogen at 77K, isothermally adsorbed and desorbed, adsorption and desorption isotherms are measured, specific surface area and pore volume are calculated using BET formula, and average pore size is calculated using BJH formula.
[0066] The ball mill adopts Juchuang environmental protection vertical planetary ball mill (JC-QM-0.4).
[0067] Example 1
[0068] The inorganic silicon source in this embodiment is silicon dioxide microspheres (Zhengzhou Fule Chemical Products Co., Ltd., average particle size 63 μm, SiO 2 The mass fraction is 98%, and the mesoporous specific surface area is 105m 2 / g);
[0069] (1) TEOS (tetraethyl orthosilicate) was dissolved in ethanol (EtOH), stirred at 25°C for 10 minutes, deionized water was added and stirred for 40 minutes, template agent TPAOH was added dropwise, the mixture was covered with a sealing film and stirred at 60°C for 6 hours to obtain a seed mother solution. In this embodiment, SiO 2 The organosilicon source is: EtOH: template: H 2 The molar ratio of O is 1:4:0.2:60; the seed crystal mother liquor obtained above is placed in a crystallization kettle, and after crystallization in an oven at 120°C for 24 hours, centrifuged, washed with deionized water, and dried to obtain seed crystals;
[0070] (2) Weighing silica, seed crystals, and water, and stirring them uniformly at 25° C.; filtering and drying the mixed solution after stirring uniformly, and calcining the dried product at 550° C. for 6 hours to obtain seed crystal silica composite particles; in this embodiment, the mass ratio of the silica particles to the seed crystals is 20:1;
[0071] (3) Weighing aluminum source aluminum isopropoxide, alkali source sodium hydroxide, and water, stirring at 25° C. for 50 minutes until the mixture is uniformly stirred; then adding seed silicon dioxide composite particles, stirring at 80° C. for 3 hours to obtain a crystallization precursor solution, wherein the pH value of the crystallization precursor solution is 11.3; in the crystallization precursor solution of this embodiment, SiO 2 The seed silica composite particles are calculated as follows: 2 O 3 The aluminum source is calculated as Na 2 The alkali source is H 2 The molar ratio of O is 1:0.015:0.15:31.3;
[0072] (4) The crystallization precursor solution is loaded into a crystallization kettle, and dynamic crystallization is first performed at 210° C. for 1 hour, and then at 170° C. for 8 hours; after the crystallization reaction is completed, the crystallized mixture is filtered, washed, and dried in sequence, and the dried crystallized product is calcined at 550° C. for 6 hours to obtain a nano ZSM-5 molecular sieve.
[0073] Example 1 The XRD spectrum of nano ZSM-5 molecular sieve is as follows Figure 1 As shown, from Figure 1 It can be seen that the nano ZSM-5 molecular sieve has the characteristic diffraction peak of ZSM-5 molecular sieve, and an obvious five-finger diffraction peak appears at 22.0-25.0°. As shown in Table 1, the relative crystallinity of the nano ZSM-5 molecular sieve in Example 1 is 66.2%.
[0074] like Figure 2 As shown, the nano ZSM-5 molecular sieve exists in a particle state, and a single particle is in the shape of a hexagonal prism, the side length of the hexagonal cross section is 155-195nm, and the height of the hexagonal prism is 125-145nm; the average particle size of the molecular sieve particles is 300nm.
[0075] like Figure 3 As shown in Table 1, the nano ZSM-5 molecular sieve has mesopores, and a hysteresis loop can be observed in the adsorption isotherm. As shown in Table 1, the micropore volume of the nano ZSM-5 molecular sieve in Example 1 is 0.10 cm 3 / g, mesopore volume is 0.10cm 3 / g.
[0076] Example 2
[0077] The inorganic silicon source in this embodiment is silicon dioxide microspheres (Zhengzhou Fule Chemical Products Co., Ltd., average particle size 55 μm, SiO 2 The mass fraction is 98%, and the mesopore specific surface area is 134m 2 / g);
[0078] (1) Preparation of seed mother solution: TEOS (tetraethyl orthosilicate) was dissolved in ethanol (EtOH), stirred at 25° C. for 10 minutes, deionized water was added and stirred for 40 minutes, template agent TPAOH was added dropwise, and then the mixture was covered with a sealing film and stirred at 60° C. for 6 hours to obtain seed mother solution. In this embodiment, SiO 2 The organosilicon source is: EtOH: template: H 2 The molar ratio of O is 1:3.7:0.19:55.4; the seed crystal mother liquor obtained above is placed in a crystallization kettle, and after crystallization in an oven at 120°C for 24 hours, centrifuged, washed with deionized water, and dried to obtain seed crystals;
[0079] (2) Weighing silica, seed crystals, and water, and stirring them uniformly at 25° C.; filtering and drying the mixed solution after stirring uniformly, and calcining the dried product at 550° C. for 6 hours to obtain seed crystal silica composite particles; in this embodiment, the mass ratio of the silica particles to the seed crystals is 16:1;
[0080] (3) Weighing aluminum source sodium aluminate, alkali source sodium hydroxide, and water, stirring at 25° C. for 50 minutes until the mixture is uniformly stirred; then adding seed silicon dioxide composite particles, stirring at 80° C. for 3 hours to obtain a crystallization precursor solution; in the crystallization precursor solution of this embodiment, SiO 2 The seed silica composite particles are calculated as follows: 2 O 3 The aluminum source is calculated as Na 2 The alkali source is H 2 The molar ratio of O is 1:0.014:0.14:28.9;
[0081] (4) The crystallization precursor solution obtained above is charged into a crystallization kettle, and is first subjected to dynamic crystallization at 210°C for 1 hour, and then to dynamic crystallization at 170°C for 8 hours; after the crystallization reaction is completed, the crystallized mixture is filtered, washed, and dried in sequence, and the dried crystallized product is calcined at 550°C for 6 hours to obtain a nano ZSM-5 molecular sieve.
[0082] As shown in Table 1, the crystallinity of the nano ZSM-5 molecular sieve in Example 2 is 81.9%; the average particle size of the nano ZSM-5 molecular sieve particles is 250 nm; the nano ZSM-5 molecular sieve has mesopores, and a hysteresis loop can be observed in the adsorption isotherm. The presence of mesopores in the sample can be observed from the pore size distribution curve; the micropore volume of the nano ZSM-5 molecular sieve is 0.12 cm 3 / g, and the mesopore volume is 0.08cm 3 / g.
[0083] Example 3
[0084] The inorganic silicon source in this embodiment is silicon dioxide microspheres (Zhengzhou Fule Chemical Products Co., Ltd., with an average particle size of 36.2 μm, SiO 2 The mass fraction is 98%, and the mesoporous specific surface area is 180m 2 / g);
[0085] (1) TEOS (tetraethyl orthosilicate) was dissolved in ethanol (EtOH), stirred at 25°C for 10 minutes, deionized water was added and stirred for 40 minutes, template agent TPAOH was added dropwise, the mixture was covered with a sealing film and stirred at 60°C for 6 hours to obtain a seed mother solution. In this embodiment, SiO 2 The organosilicon source is: EtOH: template: H 2 The molar ratio of O is 1:4.3:0.2:63.8; the seed crystal mother liquor obtained above is placed in a crystallization kettle, and after crystallization in an oven at 120°C for 24 hours, centrifuged, washed with deionized water, and dried to obtain seed crystals;
[0086] (2) Weighing silica, seed crystals, and water, and stirring them uniformly at 25° C.; filtering and drying the uniformly stirred mixed solution in turn, and calcining the dried product at 550° C. for 6 hours to obtain seed crystal silica composite particles; in this embodiment, the mass ratio of silica particles to seed crystals is 23.8:1.
[0087] (3) Weigh aluminum trichloride as an aluminum source, potassium hydroxide as an alkali source, and water, and stir at 25° C. for 50 minutes until the mixture is uniformly stirred; then add the seed crystal-silicon dioxide composite particles, and stir at 80° C. for 3 hours to obtain a crystallization precursor solution; in the crystallization precursor solution of this embodiment, SiO 2 The seed silica composite particles are calculated as follows: 2 O 3 The aluminum source is calculated as Na 2 The alkali source is H 2 The molar ratio of O is 1:0.016:0.160:33.3;
[0088] (4) The crystallization precursor solution obtained above is charged into a crystallization kettle, and is first subjected to dynamic crystallization at 210°C for 1 hour, and then to dynamic crystallization at 170°C for 8 hours; after the crystallization reaction is completed, the crystallized mixture is filtered, washed, and dried in sequence, and the dried crystallized product is calcined at 550°C for 6 hours to obtain a nano ZSM-5 molecular sieve.
[0089] As shown in Table 1, the crystallinity of the nano ZSM-5 molecular sieve in Example 3 is 93.4%; the average particle size of the nano ZSM-5 molecular sieve particles is 120 nm; from the pore size distribution curve, it can be observed that the nano ZSM-5 molecular sieve has mesopores, and a hysteresis loop can be observed in the adsorption isotherm, and the micropore volume is 0.14 cm 3 / g, and the mesopore volume is 0.08cm 3 / g.
[0090] Example 4
[0091] The method of this embodiment is the same as that of embodiment 1, except that in step (1), SiO 2 The organosilicon source is: EtOH: template: H 2 O is 1:3.3:0.16:46.8; in step (2), the mass ratio of silicon dioxide particles to seed crystals is 16.4:1; in step (3), SiO 2 The seed silica composite particles are calculated as follows: 2 O 3 The aluminum source is calculated as Na 2 The alkali source is H 2 The molar ratio of O is 1:0.012:0.12:25.6.
[0092] As shown in Table 1, the crystallinity of the nano ZSM-5 molecular sieve in Example 4 is 61.1%, and the nano ZSM-5 molecular sieve exists in a particle state with an average particle size of 380 nm. From the pore size distribution curve, it can be observed that the nano ZSM-5 molecular sieve has mesopores, and a hysteresis loop can be observed in the adsorption isotherm. The micropore volume is 0.09 cm 3 / g, and the mesopore volume is 0.11cm 3 / g.
[0093] Example 5
[0094] The method of this embodiment is the same as that of embodiment 1, except that in step (1), SiO 2 The organosilicon source is: EtOH: template: H 2 The molar ratio of O is 1:4.72:0.24:70.8; in step (2), the mass ratio of silica particles to seed crystals is 23.6:1.
[0095] As shown in Table 1, the crystallinity of the nano ZSM-5 molecular sieve in Example 5 is 70.2%, and the nano ZSM-5 molecular sieve exists in a particle state with an average particle size of 405 nm. From the pore size distribution curve, it can be observed that the nano ZSM-5 molecular sieve has mesopores, and a hysteresis loop can be observed in the adsorption isotherm, and the micropore volume is 0.09 cm 3 / g, mesopore volume is 0.10cm 3 / g.
[0096] Example 6
[0097] The inorganic silicon source in this embodiment is silicon dioxide microspheres (Zhengzhou Fule Chemical Products Co., Ltd., with an average particle size of 63 μm, SiO2 The mass fraction is 98%, and the mesoporous specific surface area is 105m 2 / g);
[0098] (1) TEOS (tetraethyl orthosilicate) was dissolved in ethanol (EtOH), stirred at 25°C for 15 minutes, deionized water was added and stirred for 30 minutes, template agent TPAOH was added dropwise, the mixture was covered with a sealing film and stirred at 70°C for 5 hours to obtain a seed mother solution. In this embodiment, SiO 2 The organosilicon source is: EtOH: template: H 2 The molar ratio of O is 1:4:0.2:60; the seed crystal mother liquor obtained above is placed in a crystallization kettle, and after crystallization in an oven at 130°C for 32 hours, centrifuged, washed with deionized water, and dried to obtain seed crystals;
[0099] (2) Weighing silica, seed crystals, and water, and stirring them uniformly at 25° C.; filtering and drying the mixed solution after stirring uniformly, and calcining the dried product at 600° C. for 6 hours to obtain seed crystal silica composite particles; in this embodiment, the mass ratio of the silica particles to the seed crystals is 20:1;
[0100] (3) Weigh aluminum source aluminum isopropoxide, alkali source sodium hydroxide, and water, stir at 25° C. for 50 minutes until the mixture is uniformly stirred; then add seed silicon dioxide composite particles, stir at 70° C. for 3 hours to obtain a crystallization precursor solution; in the crystallization precursor solution of this embodiment, SiO 2 The seed silica composite particles are calculated as follows: 2 O 3 The aluminum source is calculated as Na 2 The alkali source is H 2 The molar ratio of O is 1:0.015:0.15:31.3;
[0101] (4) The crystallization precursor solution is loaded into a crystallization kettle, and dynamic crystallization is first performed at 200° C. for 1 hour, and then at 150° C. for 8 hours; after the crystallization reaction is completed, the crystallized mixture is filtered, washed, and dried in sequence, and the dried crystallized product is calcined at 550° C. for 6 hours to obtain a nano ZSM-5 molecular sieve.
[0102] As shown in Table 1, the crystallinity of the nano ZSM-5 molecular sieve in Example 6 is 60.5%, and the nano ZSM-5 molecular sieve exists in a particle state with an average particle size of 450 nm. From the pore size distribution curve, it can be observed that the nano ZSM-5 molecular sieve has mesopores, and a hysteresis loop can be observed in the adsorption isotherm, and the micropore volume is 0.08 cm 3 / g, and the mesopore volume is 0.09cm 3 / g.
[0103] Example 7
[0104] The method of this embodiment is the same as that of embodiment 1, except that in step (1), SiO 2 Silicon source: EtOH: Template: H 2 The molar ratio of SiO2 to O is 1:2.4:0.15:84; the mass ratio of silicon dioxide particles to seed crystals in step (2) is 5:1; and the mass ratio of SiO2 to seed crystals in step (3) is 1:2.4:0.15:84. 2 The seed silica composite particles are calculated as follows: 2 O 3 The aluminum source is calculated as Na 2 The alkali source is H 2 The molar ratio of O is 1:0.015:0.15:31.3.
[0105] As shown in Table 1, the crystallinity of the nano ZSM-5 molecular sieve in Example 7 is 62.5%, and the nano ZSM-5 molecular sieve exists in a particle state with an average particle size of 400 nm. From the pore size distribution curve, it can be observed that the nano ZSM-5 molecular sieve has mesopores, and a hysteresis loop can be observed in the adsorption isotherm, and the micropore volume is 0.08 cm 3 / g, and the mesopore volume is 0.09cm 3 / g.
[0106] Example 8
[0107] The method of this embodiment is the same as that of embodiment 1, except that in step (3), the temperature of the second crystallization reaction is 170° C., and the temperature of the third crystallization reaction is 140° C.
[0108] As shown in Table 1, the crystallinity of the nano ZSM-5 molecular sieve in Example 8 is 61.7%, and the nano ZSM-5 molecular sieve exists in a particle state with an average particle size of 425 nm. From the pore size distribution curve, it can be observed that the nano ZSM-5 molecular sieve has mesopores, and a hysteresis loop can be observed in the adsorption isotherm, and the micropore volume is 0.08 cm 3 / g, and the mesopore volume is 0.09cm 3 / g.
[0109] Comparative Example 1
[0110] The preparation method of this comparative example does not include the step of preparing seed silicon dioxide composite particles; the inorganic silicon source of this comparative example adopts silicon dioxide microspheres (Zhengzhou Fule Chemical Products Co., Ltd., with an average particle size of 63 μm, SiO 2 The mass fraction is 98%, and the mesoporous specific surface area is 105m 2 / g);
[0111] (1) TEOS (tetraethyl orthosilicate) was dissolved in ethanol (EtOH), stirred at 25°C for 10 minutes, deionized water was added and stirred for 40 minutes, template agent TPAOH was added dropwise, the mixture was covered with a sealing film and stirred at 60°C for 6 hours to obtain a seed mother solution. In this embodiment, SiO 2 The organosilicon source is: EtOH: template: H 2 The molar ratio of O is 1:4:0.2:60; the seed crystal mother liquor obtained above is placed in a crystallization kettle, and after crystallization in an oven at 120°C for 24 hours, centrifuged, washed with deionized water, and dried to obtain seed crystals;
[0112] (2) Weigh aluminum source aluminum isopropoxide, alkali source sodium hydroxide, and water, stir at 25° C. for 50 minutes until the mixture is uniformly stirred; add silicon dioxide particles, stir at 80° C. for 60 minutes, then add the seed crystals in step (1), stir at 80° C. for 3 hours, and obtain a crystallization precursor solution; in this comparative example, the crystallization precursor solution is: SiO 2 Silica particles: Al 2 O 3 The aluminum source is calculated as Na 2 The alkali source is H 2 O is 1:0.015:0.15:31.3; SiO 2 The mass ratio of the silica particles to the seed crystals was 20:1;
[0113] (3) The crystallization precursor solution is charged into a crystallization kettle, and dynamic crystallization is first performed at 210° C. for 1 hour, and then at 170° C. for 8 hours; after the crystallization reaction is completed, the crystallized mixture is filtered, washed, and dried in sequence, and the dried crystallized product is calcined at 550° C. for 6 hours to obtain a ZSM-5 molecular sieve.
[0114] The SEM image of the product obtained in this comparative example is as follows Figure 4 As shown, the product obtained in Comparative Example 1 is a micron-sized ZSM-5 molecular sieve.
[0115] Comparative Example 2
[0116] The method of this comparative example is the same as that of Example 1, except that in step (4), the crystallization adopts a one-stage low-temperature dynamic crystallization, and the crystallization conditions are low-temperature crystallization at 170° C. for 9 hours.
[0117] As shown in Table 1, Figure 5 As shown, the product obtained in Comparative Example 2 is a mixture of mordenite MOR molecular sieve and ZSM-5 molecular sieve, and the crystallinity of the ZSM-5 molecular sieve is 14%.
[0118] Comparative Example 3
[0119] The method of this comparative example is the same as that of Example 1, except that in step (4), the crystallization adopts a one-stage high-temperature dynamic crystallization, and the crystallization conditions are high-temperature crystallization at 210° C. for 9 hours.
[0120] As shown in Table 1, Figure 6 As shown, no ZSM-5 molecular sieve was observed in the product obtained in Comparative Example 3, and only a mixture of MOR molecular sieve and quartz was observed.
[0121] Comparative Example 4
[0122] The preparation method of this comparative example is the same as that of Example 1, except that in step (4), the crystallization is first performed at low temperature and then at high temperature, the second crystallization reaction temperature is 170°C, and the third crystallization reaction temperature is 210°C.
[0123] As shown in Table 1, the product obtained in Comparative Example 4 is a mixture of mordenite MOR molecular sieve and ZSM-5 molecular sieve, and the crystallinity of the ZSM-5 molecular sieve is 21%.
[0124] Test Example 1
[0125] The products prepared in Examples 1-8 and Comparative Examples 1-4 were tested by XRD, SEM and low temperature nitrogen adsorption. The results are shown in Tables 1 and Figure 1-6 .
[0126] Table 1
[0127]
[0128]
[0129] According to the data in Table 1, the nano ZSM-5 molecular sieve obtained by the method disclosed in the present invention has high crystallinity, large micropore volume and mesoporous structure, and is a multi-level porous material.
[0130] Test Example 2
[0131] The products prepared in Examples 1-8 and Comparative Examples 1-4 were used for catalytic cracking, and the specific method was as follows:
[0132] First, the nano ZSM-5 molecular sieve powder prepared in Example 1 was placed in an aqueous solution of ammonium sulfate with a concentration of 0.1 g / mL (powder: ammonium sulfate mass ratio = 1:1), stirred at 80°C for 2 hours for ion exchange, and exchanged twice in total to obtain an ammonia-type nano ZSM-5 molecular sieve powder. Subsequently, the ammonia-type nano ZSM-5 molecular sieve powder was washed with water, dried, and calcined at 550°C for 4 hours to obtain a hydrogen-type nano ZSM-5 molecular sieve powder. The hydrogen-type nano ZSM-5 molecular sieve powder was tableted and sieved to obtain catalyst particles of 40-60 mesh for catalytic cracking experiments.
[0133] The catalyst particles were placed in a fixed bed reactor, the reaction pressure was 0.1 MPa, the reaction temperature was 500 °C, and the feed weight hourly space velocity (WHSV) of the raw material (1,3-diisopropylbenzene) was 80 h -1 ; The agent-oil ratio was 0.6:1 (weight ratio). After the reaction, the liquid phase material was collected by cooling, and the gas phase product was collected by drainage gas collection method. The liquid phase product was analyzed by Agilent 7890B (HP-PONA column) chromatography, and the gas phase product was analyzed by Agilent 6890 chromatography. The results are shown in Table 2.
[0134] The conversion rate of 1,3-diisopropylbenzene is calculated according to the following formula: conversion rate = 1-(mass of 1,3-diisopropylbenzene in liquid product / mass of 1,3-diisopropylbenzene raw material); benzene selectivity = mass of benzene in product ÷ (mass of 1,3-diisopropylbenzene raw material × conversion rate).
[0135] Table 2
[0136] Conversion rate (%) Benzene selectivity in product (%) Example 1 79 13 Example 2 82 15 Example 3 89 18 Example 4 72 10 Example 5 70 10 Example 6 63 9 Example 7 60 9 Example 8 61 9 Comparative Example 1 35 <3 Comparative Example 2 29 8 Comparative Example 3 <10 <5 Comparative Example 4 28 8
[0137] As shown in Table 2, when the molecular sieve product obtained by the method of the present invention is subjected to catalytic cracking reaction, the conversion rate is significantly higher than that of the comparative example under the same reaction conditions, and the benzene selectivity in the deep cracking product is significantly higher than that of the comparative example, showing a good catalytic effect. By comparing Example 1 with Example 7, it can be seen that within the ratio range of the seed mother solution and the crystallization precursor solution disclosed in the present invention and within the mass ratio range of the seed and the silica particles, when the nano ZSM-5 molecular sieve obtained is used for catalytic cracking reaction, the conversion rate is higher, and the benzene selectivity in the deep cracking product is also higher. By comparing Example 1 with Example 8, it can be seen that within the condition range of the second crystallization reaction disclosed in the present invention and the third crystallization reaction, when the nano ZSM-5 molecular sieve obtained is used for catalytic cracking reaction, the conversion rate is higher, and the benzene selectivity in the deep cracking product is also higher.
[0138] The preferred embodiments of the present disclosure are described in detail above in conjunction with the accompanying drawings; however, the present disclosure is not limited to the specific details in the above embodiments. Within the technical concept of the present disclosure, a variety of simple modifications can be made to the technical solution of the present disclosure, and these simple modifications all fall within the protection scope of the present disclosure.
[0139] It should also be noted that the various specific technical features described in the above specific embodiments can be combined in any suitable manner without contradiction. In order to avoid unnecessary repetition, the present disclosure will not further describe various possible combinations.
[0140] In addition, various embodiments of the present disclosure may be arbitrarily combined, and as long as they do not violate the concept of the present disclosure, they should also be regarded as the contents disclosed by the present disclosure.
Claims
1. A method for preparing nano ZSM-5 molecular sieve, characterized in that: The method comprises the following steps: (1) mixing an organosilicon source, ethanol and water for a first mixing, and then adding a template for a second mixing to obtain a seed crystal mother solution; subjecting the seed crystal mother solution to a first crystallization reaction, and separating seed crystals from the obtained material; (2) performing a third mixing of the seed crystals, silica particles and water to obtain a mixed solution, filtering the mixed solution, and drying and performing a first calcination treatment on the filtered solid to obtain seed crystal silica composite particles; (3) mixing an aluminum source, an alkali source and water for a fourth mixing, and then adding the seed silicon dioxide composite particles for a fifth mixing to obtain a crystallization precursor solution; (4) subjecting the crystallization precursor solution to a second crystallization reaction and a third crystallization reaction in sequence, wherein the temperature of the second crystallization reaction is higher than the temperature of the third crystallization reaction by more than 30° C.; In step (2), the average particle size of the silica particles is less than 100 μm, and the mesoporous specific surface area of the silica particles is 80 to 200 m 2 / g; the weight ratio of the silicon dioxide particles to the seed crystals is 5-30:
1.
2. The method according to claim 1, wherein: In step (1), the first mixing conditions include: stirring at a temperature of 20-35° C. for 0.5-2 h; the second mixing conditions include: stirring at a temperature of 50-80° C. for 4-8 h; In step (1), the molar ratio of the organosilicon source, the ethanol, the template and the water calculated as SiO2 is 1:(3.2-4.8):(0.16-0.24):(48-72); The conditions of the first crystallization reaction include: the first crystallization is dynamic crystallization or static crystallization, the temperature is 110-130° C., and the time is 16-72 hours; The organic silicon source is orthosilicate, and the orthosilicate is selected from one or more of tetraethyl orthosilicate and methyl orthosilicate; The template agent is a quaternary ammonium compound, and the quaternary ammonium compound is selected from one or more of tetrapropylammonium hydroxide, tetraethylammonium hydroxide and tetramethylammonium hydroxide.
3. The method according to claim 1, wherein: In step (2), the weight ratio of the silicon dioxide particles to the seed crystals is 15-25:1; the mesoporous specific surface area of the silicon dioxide particles is 90-180 m 2 / g; The third mixing conditions include: temperature of 20-35°C and time of 0.5-2h; The conditions of the first calcination treatment include: a calcination temperature of 500 to 800° C. and a calcination time of 4 to 8 hours.
4. The method according to claim 1, wherein: In step (3), the fourth mixing conditions include: stirring at a temperature of 20-35°C for 0.5-2h; the fifth mixing conditions include: stirring at a temperature of 50-80°C for 2-4h.
5. The method according to claim 1, wherein: In step (3), the aluminum source is an aluminum-containing compound selected from one or more of sodium aluminate, aluminum chloride, aluminum sulfate, aluminum isopropoxide and aluminum nitrate; and the alkali source is selected from one or more of sodium hydroxide and potassium hydroxide.
6. The method according to claim 1, wherein: In step (3), the molar ratio of the seed silica composite particles calculated as SiO2, the aluminum source calculated as Al2O3, the alkali source calculated as Na2O and the water is 1:(0.012-0.018):(0.12-0.18):(25-37.5).
7. The method according to claim 1, wherein: In step (4), the conditions of the second crystallization reaction include: temperature of 190-220°C, time of 0.5-3h, and the second crystallization reaction is dynamic crystallization; the conditions of the third crystallization reaction include: temperature of 150-180°C, time of 6-15h, and the third crystallization reaction is dynamic crystallization; the temperature of the second crystallization reaction is 30-50°C higher than the temperature of the third crystallization reaction.
8. The method according to claim 1, wherein: The method further comprises: filtering, washing, drying and performing a second calcination treatment in sequence on the product obtained in step (4); the conditions of the second calcination treatment include: a temperature of 500-600° C. and a time of 4-8 hours.
9. Nano ZSM-5 molecular sieve prepared by the method according to any one of claims 1 to 8.
10. A nano ZSM-5 molecular sieve, characterized in that: The nano ZSM-5 molecular sieve is formed into particles, and a single particle is in the shape of a hexagonal prism, the side length of the hexagonal cross section is 150-200nm, and the height of the hexagonal prism is 125-150nm; the average particle size of the nano ZSM-5 molecular sieve is 100-500nm.
11. The nano ZSM-5 molecular sieve according to claim 10, wherein: According to the crystallinity, the mass fraction of the nano ZSM-5 molecular sieve is 60-95%; the micropore volume of the nano ZSM-5 molecular sieve is 0.07-0.15cm 3 / g, and the mesopore volume is 0.06-0.12cm 3 / g.
12. Use of the nano ZSM-5 molecular sieve according to any one of claims 9 to 11 in catalytic cracking reactions.
Citation Information
Patent Citations
Molecular sieve aggregate and its preparation method
CN102872909A